Bahaya Penyebaran Informasi Hoaks dan Antisipasinya - Muharrir, Muharrir; Moulia, Nouvan; Jalaluddin, Jalaluddin; Zulfikar, Muhammad Nahyan; Adabi, Muhammad Ikhwan; Ridha, Ismu (Universitas Teuku Umar, 2024)
The spread of hoax information in Indonesia has recently increased, causing concern, especially with the ease of accessing information through various media, with social media being the primary platform for its dissemination. The active users of social media are mostly teenagers, particularly students, who are accustomed to commenting, sharing, and providing critiques on these platforms. Often, the information shared is not verified for its source, and as long as it goes viral, it is quickly spread to others. This habit can lead to the spread of unverified hoaxes, which can have negative impacts such as psychological attacks, bullying, and legal consequences for hoax spreaders under the ITE Law. Based on this issue, we conducted a community service activity using socialization and discussions about the dangers of hoax dissemination and how to anticipate them among students. The event held at SMA 2 Meulaboh went well and solemnly. The results of this activity showed that many students are still unaware of the dangers of spreading hoax information. Therefore, this initiative provided a deeper understanding, with the hope that students will become more cautious and able to filter the information circulating, especially from unknown sources.